(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Teacher efficacy has been found to be strongly linked to a variety of important educational outcomes, including instructors’ tenacity, passion, dedication, and instructional behaviour, as well as student outcomes including accomplishment, motivation, and belief in self-efficacy. Those who have attempted to examine teacher efficacy, however, have been hampered by recurring measurement issues. Many of the primary measures that have been used to capture the concept are reviewed, along with the challenges that have emerged with each. The validity and reliability results from three distinct investigations are then used to propose a promising new measure of teacher efficacy. Finally, new study possibilities made feasible by this tool are investigated.